The Effect of Social Media Use, Economic Literacy, and Self-Control on Consumptive Behavior Through Online Buying Interest in the Jepara Semarang Student Community (KMJS) (Journal of Economic Education, 2022)
Consumptive behavior occurs among teenagers today due to the rapidly growing social media for the spread of things and services. The presence of consumptive behavior does not just appear but there are factors that affect it. The aim of this research is to analyze the use of social media, literacy of economic, self-control of consumptive behavior through online buying interest. This research used a quantitative approach. The population of this research was 522 student community of Jepara Semarang (KMJS) with 226 respondents as the sample. Data collection method used questionnaire. Data Analysis used descriptive and path analysis. The result of this research showed that the use of social media has positive affects on online buying interest, economic literacy negatively affects on online buying interest, self-control negatively affects on online buying interest, the use of social media has a positive affects toward consumptive behavior through online buying interest, economic literacy has negative affects to consumptive behavior through online buying interest, the self-control has negative affects to consumptive behavior through online buying interest, online buying interest affect consumptive behavior.